Título de la tesis: “Analisis de los consumos históricos de agua potable del Cantón Catamayo.” - Sarango Guayllas, Fernando Atahualpa (2023)
The deficit in water coverage in the populations of Ecuador is the result of several factors, among the main ones are socioeconomic, socio-demographic, climatological, management, and water quality factors. In turn, the use of an outdated standard in the design of drinking water systems would aggravate the situation. For this reason, the objective of this research is to analyze the historical consumption of drinking water in the canton of Catamayo in the province of Loja. The data obtained regarding the monthly consumption of drinking water per user in the residential area of the canton by the municipal department of Drinking Water and sewerage of Catamayo corresponds to a period from January 2010 to May 2022. The primary data was manually cleaned using the Excel program to eliminate anomalous values and with the Minitab software to remove atypical data, through statistical analysis, it was established that the maximum historical consumption in the Catamayo canton was 30,175 m3 recorded in June 2020, the minimum historical consumption was in May of the same year with 11,649 m3 and the historical average was 18,444 m3. With the results obtained in the statistical analysis, the coefficient of variation of maximum daily consumption was determined for the Catamayo canton (Kd =1.64). This value, when compared to the Kd range established by the Ecuadorian standard CPE INEN 005-9-1 (1.3 - 1.5), shows that the Kd found for the canton is above the range of the standard, which evidences the existence of a deficit in water coverage. This result could generate efficient drinking water systems for the canton of Catamayo.